Region of interest video coding for low bit-rate transmission of carotid ultrasound videos over 3G wireless networks - Tsapatsoulis, Nicolas; Loizou, Christos P.; Pattichis, Constantinos S. (My University, 2007)
Efficient medical video transmission over 3G wireless is of great importance for fast diagnosis and on site medical staff training purposes. In this paper we present a region of interest based ultrasound video compression study which shows that significant reduction of the required, for transmission, bit rate can be achieved without altering the design of existing video codecs. Simple preprocessing of the original videos to define visually and clinically important areas is the only requirement
Keywords: Carotid artery; Artificial Intelligence; Algorithms